Optimization of a Controller for Marine Pollutant Monitoring Using Field Effect Devices - Alvarez, Maria Moutinho (2023)
The growing threat of heavy metal pollution in marine ecosystems demands reliable monitoring solutions due to its growing threats to aquatic ecosystems and human health. The SeaSenseX project addresses this urgency by creating a fully portable device equipped with innovative sensors, custom-made circuits and hardware components for reliable, real-time data collection and analysis. This work aims to overcome two critical challenges: simplifying the operation of an advanced technology and eliminating the dependence on laboratory-based tests, which in turn allows for the operation of users with minimal technical knowledge. A custom-made software allows for seamless integration of essential components, such as a Printed circuit board, a Charge-modulated ion sensitive fieldeffect transistor sensor, and an Arduino microcontroller. The software enables data collection, analysis and visualisation directly on-site. The versatility of the programming language Python was leveraged in the development of a reliable and intuitive guided user interface. The user can effortlessly engage with the technology through the user-friendly interface, thus bridging the accessibility gap. The results of this work have significant implications for marine pollution monitoring, offering a reliable, user-friendly tool for real-time data collection and analysis in various field scenarios. By eliminating the need to transport samples to a lab, this approach streamlines the monitoring process and empowers researchers to make informed decisions promptly. In conclusion, this work is based on the development of a the custom-made software for the control and analysis of a data acquisition system using Charge-modulated ion sensitive field-effect transistor sensors. Additionally the development and testing of the sensors was overseen. Finally, the custom-made Printed circuit boards were analysed discovering discrepancies and inefficiencies, while necessary modifications and optimizations were proposed to enhance the device’s functionality. The software allows for the integration of these components while maintaining the complexity of the device’s usage low.